Prevalencia de marcadores serológicos en donantes de sangre del Perú entre 2000 – 2020 - León Huamán, Ricardo; Del Pozo Muñoz, José Francisco; Muñoz Zambrano, María Elena; Donayre Medina, Pierina; Vega Carty, Hilary Karina (Revista del Cuerpo Médico Hospital Nacional Almanzor Aguinaga Asenjo, 2023)